Involvement of galanin and galanin receptor 1 in nociceptive modulation in the central nucleus of amygdala in normal and neuropathic rats. Issue 1 (December 2017) - Li, Shi-Yang; Huo, Mei-Ling; Wu, Xu-Yang; Huang, Yu-Qing; Wang, Lei; Zhang, Xin; Jiang, Yan-Mei; Zhang, Meng-Lin; Wang, Lin-Lin; Yu, Long-Chuan
Abstract The present study was performed to explore the role of galanin and galanin receptor 1 (GalR 1) in nociceptive modulation in the central nucleus of amygdala (CeA) in normal rats and rats with neuropathy, and the involvement of GalR 1 and PKC was also investigated. The hindpaw withdrawal latencies (HWLs) to thermal and mechanical stimulations were increased in a dose-dependent manner after intra-CeA injection of galanin in both normal rats and rats with neuropathy. The increased HWLs were significantly attenuated by intra-CeA injection of galanin receptor antagonist M40, indicating an involvement of galanin receptor in nociceptive modulation in CeA. Furthermore, intra-CeA administration of the GalR 1 agonist M 617 induced increases in HWLs in normal rats, suggesting that GalR 1 may be involved in galanin-induce antinociception in CeA. Additionally, intra-CeA injection of the PKC inhibitor inhibited galanin-induced antinociception, showing an involvement of PKC in galanin-induced antinociception in CeA of normal rats. Moreover, there was a significant increase in GalR1 content in CeA in rats with neuropathy than that in normal rats. These results illustrated that galanin induced antinociception in CeA in normal rats and rats with neuropathy, and there is an up-regulation of GalR1 expression in rats with neuropathy.